Role of Crisis Management in Reducing Socio-Psychological Vulnerabilities after Natural Disasters (Case study: Citizens of Bam City) - Seyed Rasoul Mousavi; Hamid Rashedi; Gholamreza Nabi Bidhendi (Environmental Energy and Economic Research, 2018)
Natural disasters in various forms have been identified as destructive phenomena during the life of earth planet and are also a serious threat to the inhabitants of the planet. Therefore, this issue leaded to the formation of a process called crisis management which includes activities occurring before, within and after the event to reduce the vulnerability. The country of Iran is considered as one of the world's affected countries from natural disasters due to its geographical location and climate diversity. In this research, the role of crisis management in reducing the socio-psychological vulnerability of affected citizens in 2003 earthquake of Bam city was investigated. Library and field study methods have been used to collect information in this study. Also, a qualitative-quantitative method was used to analyze the data by employing the theme method and consequently the most important factors affecting the citizen's socio-psychological vulnerabilities of Bam city after the earthquake were identified.